2001
DOI: 10.1016/s0043-1354(01)00053-7
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Models To Predict Effect of Ionic Strength on Sorption of Chlorinated Benzenes and Phenols at Sediment–Water Interface

Abstract: Abstract}It is hypothesised that the experimental sorption coefficient normalised to the organic carbon fraction of sediment (K exp oc ) for non-ionic, hydrophobic, organic pollutant depends upon the molecular properties as well as background ionic strength of the aquatic system. The utility of this concept has been demonstrated by incorporating ionic strength as a parameter in the three quantitative structure activity relationships (QSARs) namely octanol-water partitioning coefficient model (Kow model), the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Similar observations have been reported by Zhao et al [23]. Rao and Asolekar [24] studied that the effect of ionic strength on sorption of chlorinated benzenes and phenols at the sediment-water interface. They found that ionic strength had a strong effect for ionizable chemicals such as phenol as compared to that of either polarisable chemicals such as chlorobenzene or non-polar chemicals such as benzene.…”
Section: Effect Of Initial Ph and Ionic Strengthsupporting
confidence: 88%
“…Similar observations have been reported by Zhao et al [23]. Rao and Asolekar [24] studied that the effect of ionic strength on sorption of chlorinated benzenes and phenols at the sediment-water interface. They found that ionic strength had a strong effect for ionizable chemicals such as phenol as compared to that of either polarisable chemicals such as chlorobenzene or non-polar chemicals such as benzene.…”
Section: Effect Of Initial Ph and Ionic Strengthsupporting
confidence: 88%
“…Phenol and its derivatives are the major constituents of industrial wastewater produced by oil refineries, petrochemicals, polymeric resins, pharmaceuticals, coal conversion plants and chemical industries (Rajkumar and Palanivelu, 2003;Ródenas-Torralva et al, 2005;Wu et al, 2006). Their high aqueous solubility and weak adsorption to most soils result in a quick entry into groundwater due to leaching (Rao and Asolekar, 2001). The concentration of these compounds in agro-industrial wastewaters can vary from 0.05 to 10 g L À1 depending on the type and origin of the effluent.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have examined the effect of high salinity (ionic strength) on the sorption of organics (Sullivan et al, 1982;Rao and Asolekar, 2001;Turner, 2003), generally finding increased adsorption for nonpolar (i.e., more hydrophobic) organic compounds. A high K d indicates that the organic compound is likely to partition strongly onto the particular sediment.…”
Section: Sorption Onto Particulate Mattermentioning
confidence: 99%